The mediation effect of self-objectification from selfie behavior to body esteem: A relationship between selfie-behavior, self-objectification, and body esteem among female undergraduates in Malaysia - Tan, Kristin Mei Ping; He, Jing; Tan, Yuen Huey (2023)
With the increasing popularity of engaging in selfie behavior and posting them on various online platforms, there is a growing concern that such behavior may result in the heightened likelihood of individuals objectifying themselves which may contribute to one’s low body esteem, especially among females. This study investigates the relationship of the variables including selfie behavior, self-objectification, and body esteem as well as the mediation effect of self-objectification from selfie behavior on body esteem among female undergraduates in Malaysia. This study is a cross-sectional quantitative study adopting an online survey method with the use of the Qualtrics platform. The measures used to assess the variables include the Selfitis Behavior Scale (SBS), Self-Objectification Beliefs and Behavior Scale (SOBBS), and the Body Esteem Scale for Adolescents and Adults (BESAA). The data from 169 female undergraduates aged 18 to 29 (mean = 21.89; SD = 2.00) were collected through non-probability sampling. A regression analysis and PROCESS macro analysis are used to analyze the data. It was found that selfie behavior positively predicts body esteem, self-objectification negatively predicts body esteem, selfie behavior positively predicts self-objectification, and that there is a partial mediation of self-objectification from selfie behavior to body esteem. The findings of the study are all significant which provide insights into the complex dynamics of the variables and contribute to the knowledge gap of the topic which is especially limited with female undergraduates in Malaysia as the sample. Most importantly, this study is able to help improve the awareness and interventions surrounding the topic.